2021
DOI: 10.1021/acs.jcim.1c00181
|View full text |Cite
|
Sign up to set email alerts
|

xDeep-AcPEP: Deep Learning Method for Anticancer Peptide Activity Prediction Based on Convolutional Neural Network and Multitask Learning

Abstract: Cancer is one of the leading causes of death worldwide. Conventional cancer treatment relies on radiotherapy and chemotherapy, but both methods bring severe side effects to patients, as these therapies not only attack cancer cells but also damage normal cells. Anticancer peptides (ACPs) are a promising alternative as therapeutic agents that are efficient and selective against tumor cells. Here, we propose a deep learning method based on convolutional neural networks to predict biological activity (EC50, LC50, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 60 publications
(124 reference statements)
0
36
0
Order By: Relevance
“…5 , we observed that six baseline models based on QSO encoding, and three baseline models based on 1OHE, CTDD, seq2vec, and CKSAAGP encoding respectively contributed two baseline models, four encodings (DDE, CTDC, KSC, and AAC) based their respective model contributed the most in the final MLACP 2.0 prediction. The importance of physicochemical properties has been highlighted in previous studies [49] , [50] . Our analysis also indicates that CKSAAGP is one of the influential features in MLACP 2.0 performance.…”
Section: Resultsmentioning
confidence: 90%
“…5 , we observed that six baseline models based on QSO encoding, and three baseline models based on 1OHE, CTDD, seq2vec, and CKSAAGP encoding respectively contributed two baseline models, four encodings (DDE, CTDC, KSC, and AAC) based their respective model contributed the most in the final MLACP 2.0 prediction. The importance of physicochemical properties has been highlighted in previous studies [49] , [50] . Our analysis also indicates that CKSAAGP is one of the influential features in MLACP 2.0 performance.…”
Section: Resultsmentioning
confidence: 90%
“…Along these lines, peptide-protein interaction predictors are also starting to emerge to predict which peptides will interact with a certain protein and give insight into the peptide residues involved in the interaction (Casadio et al, 2022;Lei et al, 2021). Furthermore, ML is also offering ways to identify peptide sequences which are likely to have high biological activity against a particular pathology (Wu et al, 2019) (e.g., anticancer (Chen et al, 2021) or antimicrobial (Dee, 2022;E. Y. Lee et al, 2017;Plisson et al, 2020) peptides).…”
Section: Machine Learningmentioning
confidence: 99%
“…Virtual screening (Berenger and Yamanishi, 2019) 2. Anticancer peptide activity prediction (Chen et al, 2021) 3. SARS-CoV 2 inhibitor prediction (Gawriljuk et al, 2021) 4.…”
Section: Similarity-based Approachesmentioning
confidence: 99%